Analisis Penyaluran Program RTLH dalam Pandangan Ekonomi Islam di Desa Banyuwangi Kecamatan Bandongan Kabupaten Magelang - Alif Sofian; Makrifatul Ulum; Muhammad Abdul Rozaq; Mukhamat Nasikin; Dakusta Puspitasari (Jurnal Rekoginisi Ekonomi Islam, 2022)
Poverty according to islam is dangerous thing for morality,logical think,family and people. Poverty alleviation effort is the one of the main focus on islam is the existence of economic empowernment teachings for weak people. Islam views human resourches profesionally became the main agenda to empowernment poeple. One step of government policy to pressing poverty rate are through program RTLH (Rumah Tidak Layak Huni)/unhebitable house. This program is stimulant help from government to improve equitable house construction that livable from people. This research are use interview and document study metode that be held in Banyuwangi and Sukodadi vilaage.kecamatan Bandongan Kabupaten Magelang. Obstacle in RTLH program is till now increase along with high of natality rate with low of parents education. Economic development requires Islamic economic principles in managing existing resources. The principle of justice is to distribute wealth to all people so that there is no inequality of income distribution. Khalifah (leadership) that we as caliphs on this earth who have been bestowed by Allah in the form of abundant natural wealth are used as productive capital to be processed to achieve the common good.